Sociological Concepts in Guidance and Counseling: A Review of Literature - Sevilla, Gian Derick; Malazarte, Nikko; Banaag, Cecilia (JPAIR Multidisciplinary Research, 2026)
Traditionally, guidance and counseling have focused on internal and psychological processes often neglecting the impact of social environments on individual well-being. Sociology offers a vital lens through which to view clients as social actors embedded within complex societal systems. This literature review aims to analyze fundamental sociological concepts—specifically ecological systems theory, social stratification, labeling theory, and multiculturalism—and their implications for modern counseling practice. The study employed a narrative literature review, synthesizing scholarly articles from 2000 to 2025 to explore the intersection of sociological theory and mental health interventions. The analysis reveals that Bronfenbrenner’s Ecological Systems Theory facilitates a multilevel understanding of client development, while social class awareness mitigates biases and improves access to care. Furthermore, labeling theory highlights the dual role of diagnosis in both facilitating treatment and perpetuating stigma, and social justice frameworks empower counselors to address systemic barriers and oppression. The review concludes that integrating sociological perspectives transforms counseling from a remedial practice into a holistic, empowering endeavor.